Immunophenotyping in leukemia and its diagnostic significance (Medical Journal of Indonesia, 2004)
The identification of cell surface markers, defined as clusters of differentiation antigens (CDâs) could be used to classify and sub-classify leukemia. Although the same antigens are expressed on normal cells, the phenotype on malignant cells are aberrantly and frequently asynchronously expressed and may be present in combinations not observed in normal blood or bone marrow. Aberrant expression of surface antigens corresponds with poor therapeutic response and short survival. Additional surface marker analysis complementary to morphologic evaluation and cytochemical staining has greatly improved our ability to characterize hematologic malignancies. A review and illustration on the diagnostic significance of immunophenotyping in leukemia will be presented. Data from 225 patients having complete assessments including morphology, cytochemistry and immunophenotyping in the period of 1994-2001 were collected and analyzed. Based on morphologic evaluation and cytochemistry, the diagnosis of acute myeloid leukemia and acute lymphoblastic leukemia were established in 51.1% and 48.9% of cases, respectively. Based on immunophenotyping AML was found in 49.0% of the cases. ALL could be classified into 4.9% pre-B-ALL, 18.7% B-ALL, and 14.7% T-ALL. Cases expressing cross-lineage antigens were found in 12.7%. The prognostic significance of these aberrant expression of antigens for those cases has yet to be established but some of the cases responded poorly to therapy. Immunophenotyping provides the tool to: 1) distinguish normal from clonal populations of leukemic cells; 2) define lineage and reveal the stage of maturation; 3) identify inappropriate expression of lineage associated antigens; 4) provides more informations to establish diagnosis and prognosis compared to standard methods. (Med J Indones 2004; 13: 195-202) Keywords: Immunophenotyping, clusters of differentiation antigens, lineage associated antigens